Transference interpretations as predictors of increased insight and affect expression in a single case of long-term psychoanalysis - İlkmen, Yasemin Sohtorik; Halfon, Sibel (My University, 2019)
Improved insight and affect expression have been associated with specific effects of transference work in psychodynamic psychotherapy. However, the micro-associations between these variables as they occur within the sessions have not been studied. The present study investigated whether the analyst's transference interpretations predicted changes in a patient's insight and emotion expression in her language during the course of a long-term psychoanalysis. 449 thematic units from 30 sessions coming from different years of psychoanalysis were coded by outside raters for analyst's use of transference interpretations using Transference Work Scale, and patient's insight, positive emotions, anger and sadness were calculated using the Linguistic Inquiry and Word Count System. Multilevel modeling analyses indicated that transference interpretations positively predicted patient's insight and positive emotion words and negatively predicted anger and sadness. The qualitative micro-analyses of selected sessions showed that the opportunity to explore negative emotions within the transference relationship reduced the patient's avoidance of such feelings, generated insight into negative relational patterns, and helped form more balanced representations of self and others that allowed for positive feelings. The findings were discussed for clinical implications and future research directions.
Keywords: Transference interventions; Insight; Emotions; Empirical case study